Hours of recreation, vol. I A collection of transcriptions for Violine (I and II), cello and piano - SINNHOLD, Rudolf (J. Fischer & Bro., 1902)
AlonenChant sans ParolesnCharge of the HussarsnCunning Cupid-IntermezzonForget me Not-IntermezzonGavotte-IngenuenGondolieranIn Colonial daysnI would that my lovenNon e vernPostillon de LonjumeaunUnder the Palm Trees